Teaching Writing of Recount Text Using “Freeze! Freeze!” Game in Junior High School Level - Utomo, Hari Widi (CV. Ridwan Publisher, 2021)
One of the most difficult skills in English lesson is teaching writing. Therefore, this study aims to find out the effectiveness of “Freeze! Freeze!” game for teaching writing on grade eight students of SMP N 1 Rakit, Banjarnegara. This study is an experimental research at SMP N 1 Rakit. This study consisted of two groups which are experimental and control groups. In collecting the data, the writer used a test and the result was analyzed by using a t-test to find out the effect of the treatment. After analyzing the data, the writer found that there was a positive effect of the use of “Freeze! Freeze!” game in teaching writing of recount text. It could be seen from the result of hypothesis testing that the t-test was higher than the t-table (3.792>1.997). Thus, it can be concluded that the use of “Freeze! Freeze!” game in teaching writing of recount text was effective.